Cross-cultural personal selling : agents' competences in international personal selling of services - Antczak, Anna; Sypniewska, Barbara (Palgrave Macmillan, 2017)
Providing in-depth analysis, this book enables readers to understand the theoretical aspects of personal selling and explores the difficulties of selling services which are sensitive to cultural, age and gender differences, and to customers originating from diverse cultural zones. Agents and personal sellers must be aware of these differences and be familiar with the expectations of customers. Cross-cultural Personal Selling provides extensive empirical research results with special emphasis on competences, skills and qualifications of personal sellers which are necessary for successful, effective and efficient promotion campaigns aimed at customers from different cultures. Academics of international marketing and promotion will find this study extremely useful, as well as practitioners looking to expand their knowledge on personal selling.
Includes index.
Keywords: Sales management -- Cross-cultural studies.; Selling.; elektronické knihy; electronic books